Information Behavior An Evolutionary Instinct - Spink, Amanda; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Information behavior has emerged as an important aspect of human life, however our knowledge and understanding of it is incomplete and underdeveloped scientifically. Research on the topic is largely contemporary in focus and has generally not incorporated results from other disciplines. In this monograph Spink provides a new understanding of information behavior by incorporating related findings, theories and models from social sciences, psychology and cognition. In her presentation, she argues that information behavior is an important instinctive sociocognitive ability that can only be fully understood with a highly interdisciplinary approach. The leitmotivs of her examination are three important research questions: First, what is the evolutionary, biological and developmental nature of information behavior? Second, what is the role of instinct versus environment in shaping information behavior? And, third, how have information behavior capabilities evolved and developed over time? Written for researchers in information science as well as social and cognitive sciences, Spink$1 (Bs controversial text lays the foundation for a new interdisciplinary theoretical perspective on information behavior that will not only provide a more holistic framework for this field but will also impact those sciences, and thus also open up many new research directions.s
Information Behavior Framework -- Evolutionary Foundation -- Instinct Versus Environment -- Human Cognition and Social Behavior -- Lifetime DevelopmentLifetime Development -- Information Behavior Sub-processes -- Supporting Information Behavior over the Ages -- Key Propositions and Conclusions.
Keywords: Social sciences; Computer science; Library science; Anthropology; Social Sciences; Anthropology; Learning & Instruction; Computers and Society; Library Science